Strategi Guru dalam Pembinaan Karakter Siswa SMP Negeri 2 Kec. Gunuang Omeh, Kabupaten Lima Puluh Kota - Indri Prasethia; Fauzan; Alimir; Supriadi (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by the problems found in SMP Negeri 2 Kec. Gunuang Omeh related to the lack of good character of students can be seen from the morals of students who still behave less politely in speaking, lack of mutual respect, do not perform the Zuhur prayer in congregation, cheat during exams, come late to school. From the existing problems the author is interested in examining how the strategies used by teachers in character building students in SMP Negeri 2 Kec. Gunuang Omeh. This type of research is a field research, namely qualitative research where researchers observe and participate directly in the location where the data is located, whose data is obtained directly from the person being studied. The research location was conducted in SMP Negeri 2 Kec. Gunuang Omeh is located on Jalan Tan Malaka, Pandam Gadang. The informants of this research are key informants taken from the principal, teachers, and supporting informants from students. Data collection techniques in this study were observation, interviews and documentation. The data analysis technique used is data reduction which selects the data first, then displays the data which after the data is selected, summarized and concluded and presented, then data verification is drawing conclusions from the analyzed data, and the data validity technique used is by comparing observational data with interview data. Based on the results of the research that the author did, it is known that the strategies used by teachers have various kinds of character building for students at SMP Negeri 2 Kec. Gunuang Omeh is to use various types of strategies, namely exemplary strategies, habituation strategies, advice strategies, discipline strategies and using punishment strategies when students make mistakes. Keywords: Teacher Strategy, Character Building.